Peran Kepala Sekolah, Guru Dan Siswa Dalam Menerapkan Pendidikan Karakter di MI Hidayatul Ulum Kisik - Fahimatul Anis; Trapsila Siwi Hutami; Prasetyo Adi Nugroho (Jurnal Elementaria Edukasia, 2023)
One of the goals of Indonesian national education is to implement character education. Character education needs to be instilled and taught from an early age so that it becomes a habit that leads to the implementation of good educational values. The aim of this research is to analyze the role of school principals, teachers and students in implementing character education. This research method is qualitative research. The data sources for this research are school principals, teachers and students. The data collection technique uses observation and interviews. Meanwhile, data analysis uses data triangulation. In implementing character education at MI Hidayatul Ulum Kisik, the role of the principal, teachers and students has a very important role. The school principal has the main role in directing and leading the implementation of character education at the MI Hidayatul Ulum Kisik school. Teachers are the main agents in transmitting character values to students. Students have an active role in internalizing and applying character values in their lives. Therefore, the role of school principals, teachers and students has a very important role in supporting the implementation of character education in schools. The school principal plays a role in determining the school's vision which will later be used as a step in determining policy. The role of the teacher can be internalized through teaching and learning process activities in the classroom, including the value of honest character education that can be taught to students in answering questions given by the teacher who is teaching. In this way, students will be trained to behave in accordance with the values taught at school.